Biomarkers in Psoriasis: The Future of Personalised Treatment - Bikash R. Kar; Dharshini Sathishkumar; Sushil Tahiliani; Anchala Parthasarathi; Shekhar Neema; Satyaki Ganguly; K. Venkatachalam; Shrichand G. Parasramani; Haritha Komeravelli; Jaykar Thomas (Wolters Kluwer Medknow Publications, 2024)
Psoriasis is a chronic and complex immune-mediated papulosquamous disease affecting almost 2% of the world population. The interaction between a genetically predisposed individual and environmental triggers leads to a vicious cycle involving autoreactive T cells, dendritic cells, keratinocytes and dermal cells. Up to 40% of the psoriasis cases develop disabling psoriatic arthritis and an equal number of patients also tend to develop metabolic syndrome as well as cardiovascular comorbidities; hence, this is no more considered to be a disease limited to skin only. Being a systemic disease, there is an urgent need to develop potential biomarkers for the assessment of disease severity, prediction of outcome of the therapeutic intervention and association with various systemic comorbidities. Diverse genetic markers not only function as predictors of diseases pathogenesis, but also help to predict development of psoriasis and psoriatic arthritis. Personalised medicine is customising the therapeutic needs of a psoriasis patient and improving the outcome as per the hints we receive from the various biomarkers. This review deals with the list of potential biomarkers proposed to be useful in psoriasis, though there is limited data validating their routine use in clinical practice and the progress so far made in the field of precision medicine for psoriasis.